Massively parallel bisulphite pyrosequencing reveals the molecular complexity of breast cancer-associated cytosine-methylation patterns obtained from tissue and serum DNA - Korshunova, Yulia; Maloney, Rebecca K.; Lakey, Nathan; Citek, Robert W.; Bacher, Blaire; Budiman, Arief; Ordway, Jared M.; McCombie, W. Richard; Leon, Jorge; Jeddeloh, Jeffrey A.; McPherson, John D. (Genome Research, 2008)
Cytosine-methylation changes are stable and thought to be among the earliest events in tumorigenesis. Theoretically, DNA carrying tumor-specifying methylation patterns escape the tumors and may be found circulating in the sera from cancer patients, thus providing the basis for development of noninvasive clinical tests for early cancer detection. Indeed, using methylation-specific PCR-based techniques, several groups reported the detection of tumor-associated methylated DNA in the sera from cancer patients with varying clinical success. However, by design, such analytical approaches allow assessment of the presence of molecules with only one methylation pattern, leaving the bigger picture unexplored. The limited knowledge about circulating DNA methylation patterns hinders the efficient development of clinical methylation tests and testing platforms. Here, we report the results of a comprehensive methylation pattern analysis from breast cancer clinical tissues and sera obtained using massively parallel bisulphite pyrosequencing. The four loci studied were recently discovered by our group, and demonstrated to be powerful epigenetic biomarkers of breast cancer. The detailed analysis of more than 700,000 DNA fragments derived from more than 50 individuals (cancer and cancer-free) revealed an unappreciated complexity of genomic cytosine-methylation patterns in both tissue derived and circulating DNAs. Both tumor and cancer-free tissues (as well as sera) contained molecules with nearly every conceivable cytosine-methylation pattern at each locus. Tumor samples displayed more variation in methylation level than normal samples. Importantly, by establishing the methylation landscape within circulating DNA, this study has better defined the development challenges facing DNA methylation-based cancer-detection tests.
10.1101/gr.6883307